2022
DOI: 10.3390/foods11101407
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Potentially Toxic Elements in Bottled Drinking Water—Carcinogenic and Non-Carcinogenic Risks Assessment in Adults via Ingestion

Abstract: The presence of potentially toxic elements in drinking water can be dangerous for human health because of their bioaccumulation and toxicity, which is a huge concern for many researchers. In the case of bottled water, the exposure to toxic elements is achieved, especially by ingestion, leading to disorders of important functions of the human body. The aim of this study was the detection of some potentially toxic elements, from 50 samples of bottled drinking water, available on the Romanian market. Based on obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
1
1
2
Order By: Relevance
“…The levels of Pb in this study was lower than the levels reported in the studies of Annibaldi et al (2018) [ 42 ] in Italy, Bakidere et al (2013) [ 39 ] in Turkey, Ristić et al (2011) [ 38 ] in Serbia. Moreover, the Pb levels of our study were consistent with the levels reported in the studies of Ungureanu et al (2018) [ 41 ] in Romania, Hadiani et al (2015) [ 33 ] in Iran, tap water samples in Bakırdere et al (2013) [ 39 ] in Turkey and Ghaderpoori et al (2018) [ 28 ] in Khorramabad city in Iran. However, the Pb levels found in this work were higher than the levels reported by Maxwell et al (2018) [ 30 ] in Nigeria, Zazouli et al (2015) [ 40 ] in Sari city in Iran, Singla et al (2014) in India, Bamuwamye et al (2022) [ 44 ] in Uganda, Eslami et al (2022) [ 29 ], Jafarzadeh et al (2022) [ 37 ] and Maleki and Jari (2021) [ 25 ] in Iran.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The levels of Pb in this study was lower than the levels reported in the studies of Annibaldi et al (2018) [ 42 ] in Italy, Bakidere et al (2013) [ 39 ] in Turkey, Ristić et al (2011) [ 38 ] in Serbia. Moreover, the Pb levels of our study were consistent with the levels reported in the studies of Ungureanu et al (2018) [ 41 ] in Romania, Hadiani et al (2015) [ 33 ] in Iran, tap water samples in Bakırdere et al (2013) [ 39 ] in Turkey and Ghaderpoori et al (2018) [ 28 ] in Khorramabad city in Iran. However, the Pb levels found in this work were higher than the levels reported by Maxwell et al (2018) [ 30 ] in Nigeria, Zazouli et al (2015) [ 40 ] in Sari city in Iran, Singla et al (2014) in India, Bamuwamye et al (2022) [ 44 ] in Uganda, Eslami et al (2022) [ 29 ], Jafarzadeh et al (2022) [ 37 ] and Maleki and Jari (2021) [ 25 ] in Iran.…”
Section: Discussionsupporting
confidence: 91%
“…Table 6 displays other similar studies on the HMs in drinking water sources. The mean concentrations of Cr in this study was lower than the range reported by studies of Ungureanu et al (2022) in Romania [ 41 ], Maxwell et al (2018) in Nigeria and Annibaldi et al (2018) [ 42 ] in Italy conducted on the samples of marketed bottled water. However, the concentration range of Cr in this study was higher than the levels reported in the study of Ristić et al (2011) [ 38 ] in Serbia and within the concentration range reported for bottled water samples by Zazouli et al (2015) [ 40 ] in Sari city, Iran; Singla et al (2014) [ 43 ] in India; Bamuwamye et al (2022) [ 44 ] in Uganda.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations